Effects of brown algae extract to function of aorta endothelium cell in diabetic rats - Muhamad Firdaus; Made Astawan; Deddy Muchtadi; Tutik Wresdiyati; Sarwono Waspadji; Setyawati S. K. (Indonesian Journal of Pharmacy, 2010)
Macro and microvascular disease are currently the principal causes of morbidity and mortality in diabetes mellitus patients. Loss of the modulatory role of  the  endothelium  may  be  a  critical and  initiating factor  in  the  development of diabetic  vascular  disease.  Polyphenol is known behave protective active compound to function endothelium cell.  Polyphenol that contained in brown algae was phlorotannin.  The  aim  of  the  present  study  was  to  investigate  the effects  of  S.  echinocarpum extract  on  endothelial  dysfunction  in  aorta  of streptozotocin  diabetic  rats.  This experiment was conducted by complete randomized design in 2 months old of male albino Sprague Dawley strain of rats, 125-150 grams body weight. The rats divided in fivegroups, each group consist of  6  rats.  First  group:  normal  which  is  given  1  mL  of  extract  vehicle  orally; second  group:  diabetic  rats  which  is  given  1  mL  of  extract  vehicle  orally;  third group:  diabetic  rats  which  is  treated  extract  150  mg/kg  BW  dose  orally;  fourth group: diabetic rats which is treated extract 300 mg/kg BW dose orally; and fifth group: diabetic rats which is treated extract 450 mg/kg BW orally. Diabetic rats prepared by injection of 45 mg/kg  streptozotocin  intraperitoneally.  Extract was given to diabetic rats during 90 days.  The  result  showed  that  brown  algae extract  rearrange  endothelium  cell  function  of  diabetic  rats  by  increasing relaxation,  releasing  of  EDRF  and  decreasing  of  MDA.  Based on these observations,  it  was  concluded  that  S.  echinocarpum extract  recovers  the endothelial  dysfunction  associated  with  diabetes.  This effect appears to be  due to its antioxidant properties.Key words: diabetes, EDRF, endothelial dysfunction, MDA, S. Echinocarpum